Determinan Minat Mahasiswa Akuntansi Untuk Berkarier Menjadi Akuntan Publik - Bisma; Acynthia Ayu Wilasittha (JURNAL ECONOMINA, 2024)
This research aims to demonstrate the influence of internship experience, work environment, job market considerations, and motivation on the interest of accounting students from UPN "Veteran" East Java to pursue a career as Public Accountants. The population of this study consists of accounting students from the 2021 cohort at UPN "Veteran" East Java who are currently or have completed internships at Public Accounting Firms (PAFs). The research sample, comprising 50 students, was selected using simple random sampling technique. Partial Least Square was employed as the data analysis technique. The research findings indicate that only internship experience significantly influences students' interest in pursuing a career as public accountants. The reason for this influence is that accounting students who have internship experience at PAFs gain deeper insights into the career of a public accountant. For future researchers, it is recommended to include other independent variables that may affect accounting students' interest in becoming public accountants. Additionally, it is suggested to apply the research with a larger sample to obtain more valid data that can.